2008
DOI: 10.1002/eji.200737784
|View full text |Cite|
|
Sign up to set email alerts
|

Clonally expanded plasma cells in the cerebrospinal fluid of MS patients produce myelin‐specific antibodies

Abstract: Clonally expanded plasma cells (cePC) and their presumed products, oligoclonal immunoglobulin G bands (OCB), are characteristic findings in the cerebrospinal fluid (CSF) of patients with multiple sclerosis (MS). While cePC and OCB strongly suggest an involvement of B cell-dependent immune mechanisms in the pathogenesis of MS, their actual pathological relevance and target antigens remain unknown. To further understand the potential role played by cePC, we generated a panel of monoclonal antibodies (MS-mAb) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 47 publications
(60 reference statements)
3
70
1
Order By: Relevance
“…All four treatment‐naive patients with recent onset anti‐NMDAR encephalitis in the current study showed intrathecal B‐cell and plasma cell accumulation and intrathecal production of NMDAR‐specific IgG. Moreover, using single‐cell RT‐PCR of FACS‐sorted CD138 + CSF plasma cells and recombinant antibody technology,19, 21 we identified expanded clones and were able to obtain seven different rhuMab (SSM1‐7) from intrathecal cePc of one of the anti‐NMDAR encephalitis patients. Ig sequences showed varying numbers of mutations from published germline sequences, indicating antigen‐driven expansion and ongoing somatic hypermutations.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…All four treatment‐naive patients with recent onset anti‐NMDAR encephalitis in the current study showed intrathecal B‐cell and plasma cell accumulation and intrathecal production of NMDAR‐specific IgG. Moreover, using single‐cell RT‐PCR of FACS‐sorted CD138 + CSF plasma cells and recombinant antibody technology,19, 21 we identified expanded clones and were able to obtain seven different rhuMab (SSM1‐7) from intrathecal cePc of one of the anti‐NMDAR encephalitis patients. Ig sequences showed varying numbers of mutations from published germline sequences, indicating antigen‐driven expansion and ongoing somatic hypermutations.…”
Section: Discussionmentioning
confidence: 57%
“…To elucidate whether cePc are the actual source of the intrathecal autoantibody response, we cloned paired immunoglobulin heavy‐ and light‐chain variable gene regions from cePc essentially as previously described 19, 21. PEI mediated cotransfection of IgG‐HC and matching Ig‐LC expression vectors into FreeStyle 293‐F cells were carried out to produce recombinant monoclonal antibodies in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some earlier studies that evaluated whole CSF IgG from MS patients identified antibodies to several different viruses, such as measles, varicella zoster, human T-lymphocytic virus 1, and human hepatitis virus 6 (7), whereas other investigations found antibodies targeting major myelin proteins, myelin basic protein (MBP) and myelin oligodencrocyte glycoprotein (MOG) (8,9) as well as glycolipids, fatty acids, and neurofilament proteins (10). Similarly, more recent investigations that have applied single-cell PCR cloning to individual CSF B cells in MS have detected antibodies to certain viruses or myelin proteins (11)(12)(13). However, it has been impossible to match specificity of antibodies identified in CSF to OCB by studying whole CSF IgG or recombinant antibodies constructed from rearranged Ig heavy-and light-chain genes in individual B cells.…”
mentioning
confidence: 99%
“…In other words, concentrations of intrathecally synthesized IgG may reach the required lower limit for biological activity in the CSF long before any ITS is detected. Moreover, antibodies directed to extracellular targets and with predictable biological activity are retained in brain tissues 29. Recent data suggest that autoreactive antibodies spilling over from the blood at a low level owing to an intact BCB may be completely cleared from the CSF by adsorption on CNS targets 30, 31…”
Section: Discussionmentioning
confidence: 99%